Monetary Policy Credibility and the Unemployment-Inflation Tradeoff : Some Evidence From 17 Industrial Countries - N'Diaye, Papa (IMF Working Papers; Working Paper, 2002)
Using data on long-term interest rates for 17 industrial countries, this paper develops some simple measures of monetary policy credibility and then tests if such measures improve the out-of-sample forecasts of conventional models of the inflation-unemployment process. The results provide some evidence in favor of the Lucas critique by showing that the short-run unemployment-inflation trade-off tends to improve in countries that are successful in providing low and stable inflation.